Extension of first order predictive functional controllers to handle higher order internal models - Khadir, Mohamed Tarek; Ringwood, John V. (Zielona Góra: Uniwersytet Zielonogórski)
Predictive Functional Control (PFC), belonging to the family of predictive control techniques, has been demonstrated as a powerful algorithm for controlling process plants. The input/output PFC formulation has been a particularly attractive paradigm for industrial processes, with a combination of simplicity and effectiveness. Though its use of a lag plus delay ARX/ARMAX model is justified in many applications, there exists a range of process types which may present difficulties, leading to chattering and/or instability.
Keywords: model predictive control; predictive functional control; non-minimum phase systems; oscillatory systems